Stabilization of Expansive Clay Soil with Fly Ash and Ground Granulated Blast Furnace Slag Materials on UCT Values - Kusuma, Rama Indera; Abdurrohim, Abdurrohim; Vihawian, Vini; Mina, Enden; Fathonah, Woelandari (Jurnal Fondasi, 2024)
Land is one of the important elements in construction projects and must have a high bearing capacity to support the structure above it. Civil construction, whether roads, buildings, or other structures, will last a long time if one of the factors is supported by a good subgrade. The location of the road in Sudimanik Village has soil classified as expansive clay, which has a high shrinkage capacity due to changes in water content. One way to improve unstable soil is by adding materials such as Fly Ash and Ground Granulated Blast Furnace Slag (GGBFS).The purpose of this study was to determine the characteristics of the soil based on the classification and physical properties of the soil using the Unified Soil Classification System method and to determine the characteristics of the soil and the effect of adding consistent variations of fly ash at 20% and variations in the percentage of GGBFS 0%, 10%, 20%, and 30% as additional material for soil stabilization against the Unconfined Compression Test value with variations in curing time of 0, 7, 14 and 28 days.The addition of fly ash and GGBFS/slag cement substantially increased the unconfined compressive strength of the soil over time. The maximum mixture for increasing the unconfined compressive strength was achieved with 20% fly ash and 30% GGBFS in variation E, indicating that this combination is very effective for increasing the soil strength in this area.